2016
DOI: 10.1002/anie.201604848
|View full text |Cite
|
Sign up to set email alerts
|

Heteroatom Tuning of Bimolecular Criegee Reactions and Its Implications

Abstract: High-level quantum-chemical calculations have been performed to understand the key reactivity determinants of bimolecular reactions of Criegee intermediates and H X (X=O, S, Se, and Te). Criegee intermediates are implicated as key intermediates in atmospheric, synthetic organic, and enzymatic chemistry. Generally, it is believed that the nature and location of substituents at the carbon of the Criegee intermediate play a key role in determing the reactivity. However, the present work suggests that it is not on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 24 publications
(25 reference statements)
6
36
1
Order By: Relevance
“…N-H bonds in both CH 3 NH 2 and NH 3 (Scheme 2). Both OH radical and H O 2 forming paths from bimolecular Criegee reactions have previously been shown to involve similar energetic demands, [74][75][76] and thus, are equally likely to occur in the troposphere. Since the H 2 O 2 forming pathway requires the presence of two polar N-H bonds in a given amine, such a mechanistic option in the case of the Criegee-(CH 3 ) 2 NH reactions will not be available.…”
Section: Criegee-amine Interactions In the Gas Phasementioning
confidence: 99%
See 1 more Smart Citation
“…N-H bonds in both CH 3 NH 2 and NH 3 (Scheme 2). Both OH radical and H O 2 forming paths from bimolecular Criegee reactions have previously been shown to involve similar energetic demands, [74][75][76] and thus, are equally likely to occur in the troposphere. Since the H 2 O 2 forming pathway requires the presence of two polar N-H bonds in a given amine, such a mechanistic option in the case of the Criegee-(CH 3 ) 2 NH reactions will not be available.…”
Section: Criegee-amine Interactions In the Gas Phasementioning
confidence: 99%
“…The bond dissociation energy for the O-OH bond in Criegee-derived hydroperoxides is $40 kcal mol À1 . [74][75][76] Considering that the adduct in the Criegee-amine reactions is formed with an additional energy of 38.5-51.9 kcal mol À1 , the O-OH bond breakage in C(CH 3 )(H)(OOH)(CH 3 NH)-type adducts may occur under tropospheric conditions, which makes these Criegeeamine chemistries a potential source of the tropospheric OH radical. The C(CH 3 )(H)(OOH)(CH 3 NH) adduct formed from the Criegee-CH 3 NH 2 /NH 3 reaction may also decompose into H 2 O 2 and C(CH 3 )(H)(CH 3 N)/C(CH 3 )(H)(H 2 N) due to the presence of two polar Scheme 2 Plausible mechanism for the formation of low-volatility oligomers containing stabilized Criegee intermediates as repeat units during the olefin ozonolysis.…”
Section: Criegee-amine Interactions In the Gas Phasementioning
confidence: 99%
“…However, it has recently been suggested that the gas-phase reaction between Criegee intermediate or a carbonyl compound and hydrogen sulfide (H 2 S) under water or acid catalysis could account for the atmospheric formation of thioaldehydes and provide useful guidelines for efficiently synthesizing thioaldehydes within laboratory environment. 7 , 9 Criegee intermediates are formed in the cycloaddition reactions between ozone and olefins. 10 Ever since Criegee intermediates have directly been detected in the gas phase, 11 understanding their chemistry using experimental and theoretical means has become an important avenue of atmospheric research.…”
mentioning
confidence: 99%
“…Various computational studies have shown that Criegee intermediates react with organic and inorganic molecules containing polar covalent bonds with hydrogen as shown in Scheme 3 [68,93,110,[117][118][119][120][121][122]. The kinetics of insertion reactions of Criegee intermediates have been measured by various research groups using direct methods such as multiplexed photoionization mass spectrometry (MPIMS) and UV absorption spectroscopy, and the resulting rate coefficient values are summarized in a previous review (see Table 2 and Table 6 in Khan et al [26]).…”
Section: Insertion Reactionsmentioning
confidence: 99%